Perception on the behaviors and attitudes of the public towards Sarawak corridor of renewable energy (SCORE) / Zalina Ibrahim - Ibrahim, Zalina (2014)
The misconception of public about the Sarawak Corridor of Renewable Energy (SCORE) triggered the research to ponder further on the level of awareness of the Malaysian public. Thus this research aims to discover the awareness of public on SCORE project by emphasizing on public personal factors and public psychological factors. A total 362 usable questionnaires with a yield of 92.8 percent were collected throughout Sarawak 's respondents enquiring about public about their awareness of renewable energy in particular the SCORE. Using a reliability testing to confirm the reliability of questions sent out, the analysis was then analyzed using frequency, percentage and cross tabulation. The findings discovered the level of public awareness on the renewable energy and SCORE, and later discussed the personal factors and psychological factors of the respondents. The research is found to be in positive support of previous researches on renewable energy and at the same time, for some areas, provided contradiction. The research provide several conclusion and recommendation to the related parties on the SCORE development projects